1999
DOI: 10.1007/s000180050402
|View full text |Cite
|
Sign up to set email alerts
|

Minisatellite instability and germline mutation

Abstract: Tandem-repeat DNA actively turns over in the genome by a variety of poorly understood dynamic mechanisms. Minisatellites, a class of tandem repeats, have been shown to cause disease by influencing gene expression, modifying coding sequences within genes or generating fragile sites. There has been recent rapid progress towards understanding molecular turnover processes at human minisatellites. Instability at GC-rich minisatellites appears to involve distinct mutation processes operating in somatic and germline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 127 publications
(217 reference statements)
3
51
0
Order By: Relevance
“…In brief, minisatellites are thought to contribute to genome function in one of three ways: (1) Some are part of an open reading frame, which may or may not display polymorphism in the human population (for review, see Bois and Jeffreys 1999). (2) Some bind proteins with a variety of functional consequences, strongly suspected or still very hypothetical.…”
Section: Classic Definition and Early Applications Of Minisatellitesmentioning
confidence: 99%
“…In brief, minisatellites are thought to contribute to genome function in one of three ways: (1) Some are part of an open reading frame, which may or may not display polymorphism in the human population (for review, see Bois and Jeffreys 1999). (2) Some bind proteins with a variety of functional consequences, strongly suspected or still very hypothetical.…”
Section: Classic Definition and Early Applications Of Minisatellitesmentioning
confidence: 99%
“…Since homologous recombination is central to the creation and degradation of tandem repeats (Bois and Jeffreys 1999), it has been suggested that the concentrations of tandem repeats at chromosome ends might reflect these locally higher rates of recombination. Colocalization of a human hypermutable minisatellite with a nearby recombination ''hotspot'' has been reported (Jeffreys et al 1998;Jeffreys and Neumann 2005), but it is unclear how prevalent this relationship is.…”
Section: Resultsmentioning
confidence: 99%
“…The intimate role for recombination in the generation of these tandem repeats and its higher frequency near chromosome ends suggest that it could account for the nonrandom distribution of tandem repeats as noted by reports of colocalization ( Jeffreys et al 1998;Jeffreys and Neumann 2005); however, we were unable to confirm a general colocalization of tandem repeats and recombination hotspots in the human genome, which is consistent with other observations. Recombination is more frequent near chromosome ends in many organisms, yet mouse chromosomes do not exhibit a similarly higher frequency of tandem repeats near their ends (Bois and Jeffreys 1999). If higher recombination frequency is critical to creation of concentrations of tandem repeats, then the concentrations of pericentric satellite repeats are problematic to reconcile with their locations in regions with greatly suppressed recombination.…”
Section: Discussionmentioning
confidence: 99%
“…Some models have been proposed to explain the mechanisms of this migration. The transfer of a doublestranded break results in the accumulation of mutations within the minisatellite cluster, but not in other regions of genomic DNA, which explains the hypervariability of minisatellites (Bois & Jeffreys, 1999, Bois, 2003. Fig.…”
Section: Minisatellite Loci In Human Dnamentioning
confidence: 98%